(3GOGQI NWW GdYed(B.(3GdJShjb hNOeI GdYedGA(B.(3EOGQI GdhbJs - (3GdSYjO eMeO(B, (3YGWas ((3GdbGgQI(B:s (3eDSSI WjHI(B,s, 2006)
(3MOO GdNWW dRjGOI GdCQHGM hQaY caGAI GdJShjb(B-(3NOeI GdYedGA gj CSGS GdJShjb(B-(3GOGQI GdhbJs
Keywords: (3GOGQI GdhbJs; (3GdCQHGMs; (3GdJShjbs; (3NOeI GdYedGAs